2021
DOI: 10.3390/ijerph181910100
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effectiveness of the Youth Gambling Prevention Program “Who Really Wins?”—Results from the First National Implementation

Abstract: As a response to significant adolescent gambling involvement, a Croatian team of researchers and practitioners developed a universal, comprehensive, evidence-based youth gambling prevention program called “Who Really Wins?”. This study presents the results on its short-term effectiveness following the first national implementation in 18 Croatian cities, with a total of 629 high school students (66.5% male) who completed the program. A design with two measurement sessions (pre-test and post-test) was used to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 88 publications
1
11
0
Order By: Relevance
“…The provenance of the gambling addiction prevention programs analyzed was very varied: three were from Italy [40,42,44], two from the United States [31,43], two from Canada [38,39], two from Spain [34][35][36][37], two from Romania [32][33][34][35], one from Switzerland [36], one from Croatia [25], one from Portugal [41], and one from Germany [33].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The provenance of the gambling addiction prevention programs analyzed was very varied: three were from Italy [40,42,44], two from the United States [31,43], two from Canada [38,39], two from Spain [34][35][36][37], two from Romania [32][33][34][35], one from Switzerland [36], one from Croatia [25], one from Portugal [41], and one from Germany [33].…”
Section: Resultsmentioning
confidence: 99%
“…For example, the authors of [33] observed that by participating in the program, students increased their knowledge about gambling and showed a significantly decreased inclination toward gambling. Dogic-Hundric, Mandic, and Ricijas [25] reduced the cognitive distortions about gambling and the knowledge of gambling, in turn, reducing their subsequent addiction to it. No effects were observed in terms of their socio-emotional skills.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations